AMAP Assessment 2006: Acidifying Pollutants, Arctic Haze, and Acidification in the Arctic. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2006)
"This report details the results of the 2006 AMAP assessment of Acidifying Pollutants, Arctic Haze, and Acidification in the Arctic. It builds upon the previous AMAP acidification assessment presented in ‘AMAP Assessment Report: Arctic Pollution Issues’ that was published in 1998. The Arctic Monitoring and Assessment Programme (AMAP) is a group working under the Arctic Council. The Arctic Council Ministers have requested AMAP: • to produce integrated assessment reports on the status and trends of the conditions of the Arctic ecosystems; • to identify possible causes for the changing conditions; • to detect emerging problems, their possible causes, and the potential risk to Arctic ecosystems including indigenous peoples and other Arctic residents; and • to recommend actions required to reduce risks to Arctic ecosystems. This report provides the accessible scientific basis and validation for the statements and recommendations made in the AMAP Overview report, ‘Arctic Pollution 2006: Acidification and Arctic Haze’ that was delivered to Arctic Council Ministers at their meeting in Salekhard, Russia in October 2006. It includes extensive background data and references to the scientific literature, and details the sources for figures reproduced in the Overview report. It also includes conclusions and recommendations of a scientific nature, such as proposals for filling gaps in knowledge, and recommendations relevant to future monitoring and research work. Some of these are taken up in the Overview report, although that report focuses more on recommendations that specifically focus on actions aimed at improving the Arctic environment. To allow readers of this report to see how AMAP interprets and develops its scientifically-based assessment product in terms of more action-oriented conclusions and recommendations, the ‘Executive Summary of the Arctic Pollution 2006 overview report’ is reproduced in this report on pages ix to xi."